Evaluation of a candidate live attenuated influenza vaccine prepared in Changchun BCHT (China) for safety and efficacy in ferrets. Issue 48 (21st November 2016) - Shen, Zhenwei; Bowen, Richard A.; Ge, Peng; Yu, Jinfei; Shen, Yanjie; Kong, Wei; Jiang, Chunlai; Wu, Jinchang; Zhu, Changlin; Xu, Yanjun; Wei, Wei; Rudenko, Larisa; et al.
Abstract: We evaluated the safety and efficacy of a live attenuated influenza vaccine (LAIV) product in ferrets. The BCHT LAIV product was significantly less virulent than wild-type H1N1 virus, when evaluated by comparing virus shedding and histopathologic lesions. The data indicated strong evidence for an attenuated phenotype of LAIV. Furthermore, the vaccine induced robust humoral immune responses in seronegative ferrets, and protected ferrets against development of fever, weight loss and turbinate inflammatory lesions after challenging with H3N2 wide-type influenza virus. Thus, the BCHT LAIV product was safe in healthy seronegative ferrets and protected ferrets against infection of H3N2 influenza virus.